LEGAL REVIEW OF THE TERMINATION OF INVESTIGATION ORDER (SP3) REGARDING MURDER CASES (A Case Study of Murder Against Goat Thieves in Serang City) - Yuliana Riski; Hasuri Hasuri (Universitas Labuhanbatu, 2024)
This study aims to understand the termination of investigation order in the Criminal Code and analyze the Termination of Investigation Order (SP3) in Cases of Justifiable Defense Homicide. This research is descriptive with a normative juridical approach, through legislative approaches using secondary data, then analyzed qualitatively. The results show that the Serang District Attorney's Office (Kejari) issued a Termination of Investigation Order (SP3) against Muhyani (58), a farmer who stabbed a goat thief in Serang due to Justifiable Defense. Justifiable defense that exceeds limits can eliminate the criminal nature of an action and cannot be punished, so the act is not included in criminal acts according to Article 49 paragraph (1) of the Criminal Code. As stipulated in Article 109 paragraph (2) of the Criminal Procedure Code, reasons for issuing a termination of investigation letter include lack of evidence, actions that do not meet the criteria of criminal acts, or termination carried out in the interest of justiceKeywords: Termination Of Investigation Order; Forced defense; Murder